The high brightness temperature of B0529+483 revealed by RadioAstron and implications for interstellar scattering - S. V. Pilipenko; Y. Y. Kovalev; A. S. Andrianov; U. Bach; S. Buttaccio; P. Cassaro; G. Cim`o; P. G. Edwards; M. P. Gawro´nski; L. I. Gurvits; T. Hovatta; D. L. Jauncey; et al. (Oxford University Press, 2025)
The high brightness temperatures, Tb 1013 K, detected in several active galactic nuclei by
RadioAstron space VLBI observations challenge theoretical limits. Refractive scattering by
the interstellar medium may affect such measurements. We quantify the scattering properties
and the sub-mas scale source parameters for the quasar B0529+483. Using RadioAstron
correlated flux density measurements at 1.7, 4.8, and 22 GHz on projected baselines up to
240 000 km we find two characteristic angular scales in the quasar core, about 100 and 10 μas.
Some indications of scattering substructure are found. Very high brightness temperatures, Tb
≥ 1013 K, are estimated at 4.8 and 22 GHz even taking into account the refractive scattering.
Our findings suggest a clear dominance of the particle energy density over the magnetic field
energy density in the core of this quasar.
Key words: scattering – galaxies: jets – quasars: general – quasars: individual (B0529+483) –
radio continuum: galaxies.